A Literature Review on Women in Management in Asian Countries: Does Gender Matter? - Velasco, Cecilia (JPAIR Multidisciplinary Research, 2017)
The discrimination of women in the workplace is a real problem. Despite national and international organizations having made huge strides against it and implementation of United Nations Women's Treaty, apparently, nothing much has changed in the direction of eliminating it. This study aimed to find out if gender equality in terms of women representation and/or participation in the corporate world, politics, higher education management and labor workforce is practiced. Likewise, it aimed to find out the causes of inequality, if there exists. This research is essentially qualitative since it uses narrative review to assess, summarize, and interpret the results from a broad spectrum of related studies. Only 65 studies were included in the review, out of 122 studies read. The results reveal that glass ceiling and inadequate government regulations and lack of implementation of existing policies in women's leadership hinder women to forge ahead in the realm of management. This study concludes that gender inequality exists globally despite substantial national and international measures being taken against it.  Breaking the glass ceiling and fine tune the mindset of the population in favor of gender equality are highly recommended.
Keywords: Social Science; glass ceiling; cultural fit; qualitative research design; narrative review; Philippines